Peran Undang-Undang Perlindungan Data Pribadi dan Hukum Telekomunikasi dalam SPBE di Indonesia - Three Boy; Ariawan Ariawan (LPPM Universitas Ekasakti Padang, 2023)
Digital transformation is an inevitability that covers all aspects of human life with the use of Information and Communication Technology (ICT). In the era of digital transformation, implementing SPBE in Indonesia is very important to increase government accountability and the effectiveness of public services. The research was conducted using qualitative methods, which focused on using secondary sources of information from literature to investigate the material further. Currently there is a Law on Personal Data Protection, namely